Perkembangan Studi Hadis: Telaah dan Pemetaan Kajian Hadis Pada UIN Sumatera Utara - Nawir Yuslem; Ardiansyah Ardiansyah; Juriono Juriono; Uqbatul Khoir Rambe; Ismail Fahmi Arrauf Nasution (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Development of Hadith Studies: Study and Mapping of Hadith Studies at UIN North SumatraThis study aims to analyze the development of the analysis of hadith studies at UIN North Sumatra, were in its development, the study of hadith science is assumed to be in a good story, where there are only hadith study programs at the doctoral level in Indonesia; this research wants to measure how far UIN North Sumatra is in developing scientific studies hadith, how it is implemented as well as the supporting and inhibiting factors of its development. The methodology in this research is field research using an evaluation research approach, namely to design, refine, and test the implementation of a program and provide information related to educational programs that have been implemented in an institution. The procedure to be carried out in this evaluation research is to prepare an evaluation plan, verify data, analyze data and interpretation and draw conclusions. The findings of this study reveal that with limited human resources, facilities, and infrastructure, the study of hadith at UIN North Sumatra can be said to be developing rapidly and has contributed to the development of the study of hadith in North Sumatra in particular and Indonesia in general.